Origami Learning Stimulation as an Effort to Develop Early Childhood Creativity - Dwipadmini, Ade Lestari (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This study begins with a discourse in early childhood education, emphasizing the need to shift from reproductive to creative learning. Such learning should provide opportunities for exploration, reflection, and independent thinking. This article analyzes how origami can serve as both a motor skills medium and an epistemic stimulus for reflective creativity in children. The research applies a qualitative descriptive case study. Data was collected through non-participant observation, structured interviews with teachers and principals, and documentation at Kindergarten Budi Luhur Mataram. Data analysis followed an interactive process: reducing, presenting, and verifying data using source and method triangulation. Findings show that origami, combined with reflective mentoring, meaningful repetition, and non-directive teacher intervention, can shift children's creativity from imitation to self-driven. This is marked by self-correction, flexibility in motor skills, and social creativity through mutual assistance. The main contribution is the creation of a stimulus–response–reflection–actualization framework for early childhood creativity. These results highlight that creativity grows not just from the media, but from learning interactions that view children as creative subjects, not just instruction followers.